Efek Narsisme dan Psikopati Terhadap Praktik Tidak Etis Akuntan - Adrian Yudisthira; Tan Ming Kuang (Owner : Riset dan Jurnal Akuntansi, 2023)
Personality factors play an important role when a person is faced with a situation that involves moral judgment of right or wrong. A person with dark personality characteristics (dark triad) is very likely to exhibit unethical behavior. Ethical behavior is an important issue for the accountant profession because published financial statements must be accountable to the public, especially for investors and creditors as parties who bear great risks in making their investment and credit decisions. Although many studies have examined the factors causing the unethical behavior of accountants, studies investigating the impact of accountants' dark personalities on ethical decision-making are still scarce. This study aims to examine the effect of two types of dark personalities, namely narcissism and psychopathy, on accountant decision making involving various business ethical situations. The study employed a quantitative approach with primary data obtained from questionnaires. Narcissism is measured through Narcisstic Personality Inventory, psychopathy is measured through Levenson Self-Report Psychopaty Scale, and attitude toward unethical practices used an instrument use d by Bailey (2019). The population was management accountants, public accountants, and public sector accountants with a sample of 103 respondents. Multiple linear regression analysis was performed to test the research hypotheses using SPSS software version 26. The results showed that accountants with dominant narcissistic and psychopathic personalities tend to make unethical decisions.